ANALISIS KESUKSESAN SISTEM INFORMASI MANAJEMEN DAERAH DENGAN MENGADOPSI MODEL DELONE & MCLEAN - Yasa, I Wayan Eka Suputra; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The success of an Accounting Information System (AIS) on financial management in government institutions is important to be noticed. Especially, if there was a transition of system usage from one to another. It is because the degree of the system’s success can determine performance of the employee. The aim of this study is to assess the success of the SIMDA through DeLone & McLean Information System Success Model (2003). This research conducted at Regional Secretariat of Finance Department in Gianyar regency. This research took a sample based on non-probability method, using the saturation sampling technique. The data is analyzed using multiple linear regression analysis. This research find out information quality affect system use, also system use and user satisfaction affect individual performance. The success of SIMDA which measured by the affect of system use and user satisfaction to the individual performance result that the implementation of SIMDA has been successful
Keywords: DeLone & McLean Information Success Model, SIMDA, The Success of AIS,Individual Performance